Evaluasi Kesesuaian Lahan untuk Tanaman Kelapa Sawit dengan Tanaman Tumpang Sari Kacang Kedalai di Desa Engkadu Kecamatan Ngabang Kabupaten Landak - Ponda, Ponda; Hazriani, Rini; Agustine, Leony (Pedontropika: Jurnal Ilmu Tanah dan Sumber Daya Lahan, 2026)
Land is a limited natural resource, so its utilization needs to be planned optimally and sustainably. The decline in oil palm productivity and the increasing demand for food encourage the need for alternative land use through intercropping systems with food crops, one of which is soybeans. This study aims to evaluate the actual and potential land suitability for oil palm and soybean crops in an intercropping system in Engkadu Village, Ngabang District, Landak Regency. The research methods include field surveys, soil sampling and analysis, slope class determination, and land suitability mapping using the FAO (1976) approach and the BBSDLP Technical Guidelines (2011). Evaluation was carried out on physical and chemical parameters of the soil which were then compared with the land suitability criteria for both commodities. The results show that the actual land suitability classification at SL 1 and 2 for oil palm crops is classified as a class within the subclass S2-na, nr, wa. The actual land suitability classification at SL 1 and 2 for soybean crops is classified as a subclass within N-wa. Improvement efforts can be carried out by providing organic materials, liming, fertilizing, making drainage channels, making terraces, planting ground cover plants, recommending the use of oil palm land and replanting oil palm plants that are more than 20 years old.